2018
DOI: 10.1016/j.mad.2018.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Caloric restriction and cellular senescence

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 90 publications
0
58
0
Order By: Relevance
“…The spectrum of cell senescence has been widened by studies showing that post-mitotic neurons may also display a senescent phenotype that can be ameliorated by a hypocaloric diet [107]. The mechanisms by which caloric restriction may reduce the appearance of new senescent cells include a reduction of ROS from nutrient metabolism, stimulation of autophagy, increased expression of sirtuins, and enhancement of normal DDR mechanisms [108]. At the organismal level, caloric restriction leads to reductions in bioavailable IGF-1 [109], a known inducer of cellular senescence over the long term [66].…”
Section: How Can We Fight Cellular Senescence?mentioning
confidence: 99%
“…The spectrum of cell senescence has been widened by studies showing that post-mitotic neurons may also display a senescent phenotype that can be ameliorated by a hypocaloric diet [107]. The mechanisms by which caloric restriction may reduce the appearance of new senescent cells include a reduction of ROS from nutrient metabolism, stimulation of autophagy, increased expression of sirtuins, and enhancement of normal DDR mechanisms [108]. At the organismal level, caloric restriction leads to reductions in bioavailable IGF-1 [109], a known inducer of cellular senescence over the long term [66].…”
Section: How Can We Fight Cellular Senescence?mentioning
confidence: 99%
“…However, the molecular mechanisms underlying the beneficial effects of CR on ARHL remain incompletely understood. Metabolic alterations by stimulating metabolic regulator proteins such as SIRT1, AMP‐activated protein kinase (AMPK), and PPARγ coactivator‐1α (PGC‐1α), which occur as part of the adaptation to CR, potentially underlie the efficacy of CR (Fontana, Nehme, & Demaria, ). These observations suggest that alterations of mitochondrial energy metabolism play a critical role in CR response.…”
Section: Introductionmentioning
confidence: 99%
“…These observations suggest that alterations of mitochondrial energy metabolism play a critical role in CR response. In fact, CR has been shown to protect mitochondrial function from age‐dependent decline, reduce mtDNA damage, reverse many changes in mitochondrial gene expression, and cause metabolic changes to increase energy metabolism, delaying aging in mammals (Fontana et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that DR delayed cancer progression in humans and experimental models by decreasing the rate of aging [50,51]. DR induced FGF21 and AMPK, protecting from aging-related cell dysfunction and exhibiting anti-inflammatory and antitumorigenic properties.…”
Section: Discussionmentioning
confidence: 99%